An investigation into harvesting energy from sleeper vibration due to a passing train - Cleante, Vinícius Germanos (2019)
The advances in microelectromechanical systems to power supply devices for monitoring the structural integrity, mainly for applications in remote areas or with difficult access, have made energy harvesting from ambient vibration a highly researched topic. Although several electromechanical mechanisms have been proposed for applications in a variety of fields, harvesting energy from railway track vibrations is relatively new, and only a small amount of research is ongoing in this topic. This thesis aims to determine the factors that govern the sleeper vertical vibration induced by a passing train, develop a methodology to emulate this vibration in a laboratory-based system and to derive a model of a load resistance attached to a linear electromagnetic transducer to determine the optimum energy harvested. The study shows the importance of knowing the vibration behaviour of the sleeper in order to tune the energy harvester to the correct excitation frequency. A comparison between piezoelectric and electromagnetic transducers is performed using a two-port network model to determine which transducer performs better for low frequency vibration. To emulate sleeper vibration due to a passing train using an electrodynamic shaker, a compensator filter is designed to remove the system dynamics. An analytical investigation into the energy dissipated by a load resistance attached to an electromagnetic transducer when subject to a time-limited base excitation, which may include the transient and steady-state responses, is carried out and compared with numerical analysis. This is validated with an experimental test in the laboratory-based system. This work has shown that in order to harvest the maximum energy from the vibrating source, the electromagnetic transducer must operate in the transient regime and its natural frequency should be tuned to the frequency with the largest acceleration amplitude. This was found to be achieved only using an ideal transducer. When the device is operating in a regime which may include or be only the steady-state, due to the internal coil resistance or, mainly, due to the mechanical damping, the transducer may perform better when the natural frequency is tuned to the frequency with the largest velocity amplitude. For the case studied in this work, from the sleeper vertical vibration induced due to the passage of an Inter-city train travelling at Steventon site, the 3rd trainload frequency has the largest velocity amplitude and the 7th trainload frequency has the largest acceleration amplitude.